"A Parliament of Monsters": Genre, Disability, and the Revival of Epic Ability in Wordsworth’s Prelude - Toscano, Pasquale S. (Disability Studies Quarterly, 2019)
Although scholars addressing William Wordsworth's shorter lyrics have traditionally praised his positive treatment of physical otherness, at least one commenter writing on The Prelude correctly characterizes Wordsworth's depiction of disabled individuals as "demonic" (Curran 184). This is a divide that as of yet has not been properly explicated, and one which I attribute to the shift in genre, from lyric to epic, which superimposes onto The Prelude pre-drawn battle-lines between the virile hero and the sluggishly-monstrous, aberrant creatures who stand in his way. Indeed, the poet's consistent stigmatization of disability coupled with an equally persistent insistence that physical ability is fundamental to his epic endeavor situates The Prelude more squarely within the epic tradition than previously noticed. As in the works of poetic forbears, disabled characters nearly derail Wordsworth from his epic project—the development of the poet's mind via the instruction of nature. But more importantly, it is Wordsworth's commentary on how one can most successfully participate in the natural world that definitively excludes physically-othered individuals from achieving even a romanticized iteration of heroic status. By the end of this essay, then, it will become clear that The Prelude, which many scholars consider to be extending Milton's epic turn inward in Paradise Lost, depends far more upon the physical realm, and ability, than previously believed.